Non-targeted screening of plastic-related chemicals in food collected in Montreal, Canada. (1st October 2020) - Tian, Lei; Zheng, Jingyun; Goodyer, Cindy Gates; Bayen, Stéphane
Highlights: A non-targeted workflow was applied to study plastic-related chemicals in food. BPA, BPS, bis(2-ethylhexyl) adipate, dibutyl adipate, hexadecyl methacrylate and Irganox®1076 measured. All six compounds detected in food collected in Montreal, Canada. For the first time BPS was reported in Canadian fresh fish from markets. Abstract: A non-targeted screening method based on ultrasound-assisted extraction followed by high-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (HPLC–QTOF-MS) was developed to screen for the presence of plastic-related chemicals (PRCs) in different types of food (fish, chicken, canned tuna, leafy vegetables, bread and butter). Eleven bisphenols were used as targeted compounds. Instrument linearity ( r 2 ≥0.98), inter-day precision (RSD ≤9.0%) as well as method detection limits (MDLs below 3.6 ng g −1 ) were satisfactory. Recoveries of the eleven bisphenols ranged from 76% to 122% among the different food matrices. The method was applied to food collected from Montreal, Canada in 2017–2018. The non-targeted screening approach identified a range of contaminants in different food matrices, including BPA, BPS, bis(2-ethylhexyl) adipate, dibutyl adipate, hexadecyl methacrylate and Irganox®1076. Further research is suggested to investigate the concentration of these PRCs, the consumption habits of average and specific populations and the potential routes of contamination.